(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
Groundwater resources have become an important fresh water supply due to its increasing demands for agricultural, drinking and industrial uses. Groundwater is often contaminated by the process of industrial development and suburbanization that has gradually advanced over time without any concern for environmental consequences. The objective of this study is to analyse the groundwater quality of shallow dug wells in parts of Tanah Merah district by conducting quality assessment of groundwater using WHO and MHO guide lines. Groundwater samples were collected from dug wells uniformly spread out across the study area to investigate the major ion chemistry of the groundwater as well as physical parameter. The major ion being investigated are sodium, magnesium, calcium, potassium, sulphate, nitrate, chloride and bicarbonates. Various methods have been were employed to determine the major ions concentration in the samples such as atomic absorption spectrophotometer for cations, gravimetric method for sulphates, titration method for chloride and bicarbonates and colorimetric method for nitrate ion. From the analysed data’s, most wells are safe for drinking purpose although quite a small amount of ion concentration has surpassed the permissible limit set by WHO and MOH. The graphical presentation of major ion chemistry aids in identifying two types of groundwater. Ionic species such as Na-K-HCO3 and mixed type waters are likely to occur in the groundwater system. The analysed major ions concentrations indicates that majority of the shallow dug wells reported adequate or lower values compared to permissible limit which are safe and can be utilized for various domestic purposes including drinking. Several recommendations has been suggested to proliferate the groundwater quality such as strictly monitoring and supervising the dissipation of waste such as pesticides, industrial effluent and domestic sewage into the aquifer.